A base-band I- Q GMSK modulator study / Shipun Anuar Hamzah, Mohd Shamian Zainal and Mahamod Ismail - Hamzah, Shipun Anuar; Zainal, Mohd Shamian; Ismail, Mahamod (2006)
This paper presents the I - Q Gaussian Minimum Shift Keying (I - Q GMSK) modulation technique. GMSK is a widely used modulation scheme because of its constant envelope property and spectral efficiency. We provide some simulation results of I-Q GMSK modulator which consists of ADC, NRZ -L, Gaussian LPF, integrator, computation of In-phase, and Quadrature-phase terms by using Matlab program. Then, this result is compare with the I-Q MSK modulator signal.